Progressive derivation of serially homologous neuroblast lineages in the gnathal CNS of Drosophila. - Christof Rickert (PLoS ONE, 2018)
Along the anterior-posterior axis the central nervous system is subdivided into segmental units (neuromeres) the composition of which is adapted to their region-specific functional requirements. In Drosophila melanogaster each neuromere is formed by a specific set of identified neural stem cells (neuroblasts, NBs). In the thoracic and anterior abdominal region of the embryonic ventral nerve cord segmental sets of NBs resemble the ground state (2nd thoracic segment, which does not require input of homeotic genes), and serial (segmental) homologs generate similar types of lineages. The three gnathal head segments form a transitional zone between the brain and the ventral nerve cord. It has been shown recently that although all NBs of this zone are serial homologs of NBs in more posterior segments, they progressively differ from the ground state in anterior direction (labial > maxillary > mandibular segment) with regard to numbers and expression profiles. To study the consequences of their derived characters we traced the embryonic lineages of gnathal NBs using the Flybow and DiI-labelling techniques. For a number of clonal types serial homology is rather clearly reflected by their morphology (location and projection patterns) and cell specific markers, despite of reproducible segment-specific differences. However, many lineages, particularly in the mandibular segment, show a degree of derivation that impedes their assignment to ground state serial homologs. These findings demonstrate that differences in gene expression profiles of gnathal NBs go along with anteriorly directed progressive derivation in the composition of their lineages. Furthermore, lineage sizes decrease from labial to mandibular segments, which in concert with decreasing NB-numbers lead to reduced volumes of gnathal neuromeres, most significantly in the mandibular segment.